Formation of multiple or adventive embryos in Epidendrum nocturnum Jacq (Orchidaceae) - Stort, M. N. Silva; Pavanelli, E. A. Dos Santos (My University, 1985)
Under greenhouse conditions, Epidendrum nocturnum Jacq. plants produce fruits by both self-fertilization and cleistogamy. Although adapted to these reproductive processes the species respond also to cross-pollination. Seeds without embryos and with one embryo are usual but occasionally seeds with two, three or four embryos are produced. Multiple embryos are formed by polyembryony and apomixis. © 1985 Annals of Botany Company.
Keywords: Apomixis; Cleistogamy; Epidendrum nocturnum; Polyembryony; Self-pollination; Supernumerary embryos